2007
DOI: 10.1128/jvi.00807-07
|View full text |Cite
|
Sign up to set email alerts
|

Latent Infection of a New Alphanodavirus in an Insect Cell Line

Abstract: Insect BTI-TN-5B1-4 (Tn5) cells have been used extensively with recombinant baculoviruses to express foreign genes. When a recombinant baculovirus containing the hepatitis E virus capsid protein gene was used to infect Tn5 cells, unknown virus particles in addition to the anticipated hepatitis E virus-like particles were produced in the infected cells. The unknown virus particles were 35 nm in diameter and contained RNA that was highly homologous to full-length RNA1 (3,107 bp) and RNA2 (1,383 bp) genomic RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 32 publications
(35 reference statements)
5
78
0
Order By: Relevance
“…We thus suspect that our Sf21 cell line has a low-level persistent infection with FHV, as has been demonstrated for other cell lines (26). We also built contigs from the NωVVLP-RNAseq reads that bore weak protein homology to other Rhabdoviridae and so may reflect a low-level infection with an unknown insect virus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We thus suspect that our Sf21 cell line has a low-level persistent infection with FHV, as has been demonstrated for other cell lines (26). We also built contigs from the NωVVLP-RNAseq reads that bore weak protein homology to other Rhabdoviridae and so may reflect a low-level infection with an unknown insect virus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that relatively large numbers of overlapping baculovirus transcripts occur in the AcMNPV infection cycle (33), potentially resulting in dsRNA and a RNAi response. In addition, it was also previously observed that an alphanodavirus (TNCL virus) that persistently infects Tn5B1-4 cells appears to be released from suppression upon infection of the cell by AcMNPV (78). Previous studies have also documented viral siRNAs directed against specific hotspots in the Helicoverpa armigera SNPV (HaSNPV) genome (77).…”
Section: Assembly and Annotation Of The T Ni Tnms42 Transcriptomementioning
confidence: 95%
“…For calibration of the transfection efficiency, pEA-polyhedrin-MycHis was cotransfected with an expression vector that encodes the capsid protein of Flock House virus (FHV) fused to a C-terminal MycHis tag (pEA-FHV-CP-MycHis). The capsid protein of FHV was amplified from cDNA of persistently infected Hi5 cells (27) using 5=-AATTGGATCCCAACATGGTCAACAAC AGCAGACCAAAAC-3= (forward) and 5=-AATTGGATCCGTCTAAAA TCCAAAACCTTCAAATAG-3= (reverse) as primers, and the PCR fragment was subcloned into the BamHI site of the pEA-MycHis vector as described for BmCPV polyhedrin.…”
Section: Methodsmentioning
confidence: 99%